Repeated methamphetamine treatment increases spine density in the nucleus accumbens of serotonin transporter knockout mice - Yoshiyuki Kasahara; Yasufumi Sakakibara; Takashi Hiratsuka; Yuki Moriya; Klaus‐Peter Lesch; F. Scott Hall; George R. Uhl; Ichiro Sora (Wiley, 2019)
Abstract Aim Repeated psychostimulant drug treatment, including methamphetamine, in rodents readily produces behavioral sensitization, which reflects altered brain function caused by repeated drug exposure. Dendritic remodeling of medium spiny neurons in the nucleus accumbens is thought to be an essential mechanism underlying behavioral sensitization. We recently showed that chronic methamphetamine treatment did not produce behavioral sensitization in serotonin transporter knockout mice. Methods In this study, we report the spine density of medium spiny neurons in the nucleus accumbens after repeated methamphetamine injection to examine morphological alterations in serotonin transporter knockout mice. Results Golgi‐COX staining clearly showed that the spine density of medium spiny neurons in the nucleus accumbens increased following repeated methamphetamine treatment in both wild‐type and serotonin transporter knockout mice. Conclusions Our results suggested that augmented serotonergic neurotransmission produced by serotonin transporter deletion prevents the development of behavioral sensitization in a manner that is independent of dendritic remodeling in the nucleus accumbens.